Exploring the predictive power of EFL teachers' work engagement and buoyancy in their professional development - Zhang, Xiaojuan; Yang, Lei; Ergun, Anna Lia Proietti (UNIV GRANADA, 2023)
The complexities and constant changes of trends in teaching the English language demand teachers to work on their pedagogical knowledge and skills continuously. These are best obtainable in professional development programs. However, the role of teacher emotions in such programs has remained unaddressed. To bridge this gap, this study examined the predicating role of second language (L2) teachers' work engagement and buoyancy in their professional development. A total of 348 Chinese teachers participated in a survey with three online questionnaires. The results of structural equation modeling (SEM) and regression illustrated that both teacher work engagement and buoyancy could predict L2 teachers' professional development. In particular, it was found that about 68% and 61% of changes in TPD could be predicted by work engagement and buoyancy, respectively. The study is momentous for L2 teaching and teacher education by calling for the integration of emotions into TPD and pedagogy.
Keywords: buoyancy; EFL teachers; Positive psychology; Professional development; SEM; Work engagement; ACADEMIC BUOYANCY; EMOTIONS; DYNAMICS; Education & Educational Research; Linguistics